Smoke aerosols elevate precipitation top and latent heat to the upper atmosphere globally - Hongxia Zhu; Hongwei Zhao; Shuping Yang; Renjun Zhou; Yu Wang; Yufei Zou; Chun Zhao; Rui Li (npj Climate and Atmospheric Science)
Abstract Investigations across five fire-impacted regions worldwide show that smoke consistently increases precipitation rates at elevations above the 0 °C isotherm. This enhancement persists despite regional differences in atmospheric circulation fields associated with precipitation events. Upon limiting dynamic variations, the enhancement of upper-level precipitation rates by smoke aerosols remained evident. Generally, wildfire emissions were estimated to augment the global mean annual Aerosol Optical Depth by 0.0358, with a variation of 0.56%, and to lower the mean annual global precipitation top temperature by 0.32 °C, with a variation of 3%. It suggests that on the global stage, smoke aerosol acts as an effective cloud condensation and ice nucleating agent, diminishing cloud particle sizes at the lower layer, facilitating the formation of ice-phase hydrometeors, and triggering augmented latent heat release at the upper layer, which delay the rain formation from low to high altitude, and enhance the upper-level rain intensity and elevate precipitation tops.